Utilization of poultry waste as a source of biogas production. (2021) - Gohil, Arka; Budholiya, Sejal; Mohan, C.G.; Prakash, R.
Abstract: The present study aims to explore the use of poultry and domestic waste to produce the biogas. The current rate of diesel consumption is quite high while taking into account the gas emissions and the fast depletion of non-renewable fuel sources. The study conducted is about adding a certain optimal amount of bio-gas from the poultry waste to the gas mixture from the carburettor to reduce the fuel consumption. The greatest biogas generation potential for the dairy animal's excrement and poultry dropping blend is in the request of 25% CD + 75% PL, >50% CD + 50% PL, >00% CD + 100% PL. The two-composition mixture of 20% and 30% biogas with air shows that the amount of diesel consumption is reduced. The highest reduction at 20% biogas and at zero load stands at 29% less diesel consumption and 30% biogas mixture and at zero load, 37.5% fuel reduction.